2020
DOI: 10.1111/jocs.14730
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of truncus arteriosus repair and predictors of mortality

Abstract: Objective The objective of this study was to identify patient and hospitalization characteristics associated with in‐hospital mortality in infants with truncus arteriosus. Methods We conducted a retrospective analysis of a large administrative database, the National Inpatient Sample data set of the Healthcare Cost and Utilization Project for the years 2002 to 2017. We also sought to evaluate the resource utilization in the subgroup of subjects with truncus arteriosus and 22q11.2 deletion syndrome. Neonates wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…DiGeorge syndrome is also a risk factor for both gastrostomy and tracheostomy after complete repair of tetralogy of Fallot (13). In a recent study recent study that utilized the National Inpatient Sample dataset, patients with DiGeorge syndrome undergoing truncus arteriosus repair had higher rates of gastrostomy and tracheostomy compared with those without DiGeorge syndrome (14). Our findings support the high burden of disease DiGeorge syndrome adds to patients with conotruncal heart defects.…”
Section: Discussionmentioning
confidence: 99%
“…DiGeorge syndrome is also a risk factor for both gastrostomy and tracheostomy after complete repair of tetralogy of Fallot (13). In a recent study recent study that utilized the National Inpatient Sample dataset, patients with DiGeorge syndrome undergoing truncus arteriosus repair had higher rates of gastrostomy and tracheostomy compared with those without DiGeorge syndrome (14). Our findings support the high burden of disease DiGeorge syndrome adds to patients with conotruncal heart defects.…”
Section: Discussionmentioning
confidence: 99%
“…In aggregate, these 15 articles collectively represented 4,999 patients, with a slight male predominance at 54%. Notably, one study reported the largest cohort with 3,009 patients 37 .…”
Section: Study Selectionmentioning
confidence: 99%
“…The incidence of non-cardiac complications was also greater. Hamzah and colleagues reported a postsurgical mortality rate from 6.9 to 11% [ 76 , 77 , 78 ]. Particularly, the authors highlighted significant in-hospital mortality (more than 10% of cases).…”
Section: Outcome Of Cardiac Surgery In 22q112 Deletion Syndromementioning
confidence: 99%